Gain of function of ASXL1 truncating protein in the pathogenesis of myeloid malignancies - Yang, Hui; Kurtenbach, Stefan; Guo, Ying; Lohse, Ines; Durante, Michael A.; Li, Jianping; Li, Zhaomin; Al-Ali, Hassan; Li, Lingxiao; Chen, Zizhen; Field, Matthew G.; Zhang, Peng; et al. (Blood, 2018)
Additional Sex Combs-Like 1 (ASXL1) is mutated at a high frequency in all forms of myeloid malignancies associated with poor prognosis. We generated a Vav1 promoter-driven Flag-Asxl1Y588X transgenic mouse model, Asxl1Y588XTg, to express a truncated FLAG-ASXL1aa1-587 protein in the hematopoietic system. The Asxl1Y588XTg mice had an enlarged hematopoietic stem cell (HSC) pool, shortened survival, and predisposition to a spectrum of myeloid malignancies, thereby recapitulating the characteristics of myeloid malignancy patients with ASXL1 mutations. ATAC- and RNA-sequencing analyses revealed that the ASXL1aa1-587 truncating protein expression results in more open chromatin in cKit+ cells compared with wild-type cells, accompanied by dysregulated expression of genes critical for HSC self-renewal and differentiation. Liquid chromatography–tandem mass spectrometry and coimmunoprecipitation experiments showed that ASXL1aa1-587 acquired an interaction with BRD4. An epigenetic drug screening demonstrated a hypersensitivity of Asxl1Y588XTg bone marrow cells to BET bromodomain inhibitors. This study demonstrates that ASXL1aa1-587 plays a gain-of-function role in promoting myeloid malignancies. Our model provides a powerful platform to test therapeutic approaches of targeting the ASXL1 truncation mutations in myeloid malignancies. •Transgenic expression of ASXL1aa1-587 truncating protein in the hematopoietic system leads to diverse myeloid malignancies in mice.•ASXL1aa1-587 gains an interaction with BRD4 and Asxl1Y588XTg hematopoietic stem/progenitor cells are hypersensitive to BET bromodomain inhibitors.